Sosialisasi Dampak E-sports pada Anak Sekolah Dasar - Fajar Hamdhan Utama; Septyaningrum Putri Purwoto; Heni Yuli Handayani; Haryo Mukti Widodo (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2022)
Esports or electronic sports are types of sports based on electronic equipment such as PCs (computers), cellphones (mobile phones) or such as PlayStation or Xbox. Esports is growing rapidly in Indonesia. Games that are often played include Mobile Legend, PUBG Mobile, Free Fire and Dota. This game is even in demand in all circles, be it children, teenagers and parents. Most children often forget the time when they have played the game. This dedication to socializing the impact of esports has been successful. This is because it makes students understand more about the impact of esports for elementary school children, besides that students can also find out how to overcome the addiction to playing esports.